2022
DOI: 10.1093/gerona/glab386
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis Integrated With Multi-omics Data Analysis to Elucidate Pathogenic Mechanisms of Age-Related Knee Osteoarthritis in Mice

Abstract: Increased mechanistic insight into the pathogenesis of knee osteoarthritis (KOA) is needed to develop efficacious disease-modifying treatments. Though age-related pathogenic mechanisms are most relevant to the majority of clinically-presenting KOA, the bulk of our mechanistic understanding of KOA has been derived using surgically induced post-traumatic OA (PTOA) models. Here, we took an integrated approach of meta-analysis and multi-omics data analysis to elucidate pathogenic mechanisms of age-related KOA in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 101 publications
2
8
0
Order By: Relevance
“…1F ) 18 . A recent systematic review identified elevated inflammation, increased senescence, and impaired autophagy as common denominators associated with aging-induced KOA in mice 19 , all of which are downstream of α-Klotho 20 – 24 . When we accessed archived microarray data (GSE80285) 25 , we found that inhibition of α-Klotho protein significantly activated PI3K/Akt signaling in human primary chondrocytes in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1F ) 18 . A recent systematic review identified elevated inflammation, increased senescence, and impaired autophagy as common denominators associated with aging-induced KOA in mice 19 , all of which are downstream of α-Klotho 20 – 24 . When we accessed archived microarray data (GSE80285) 25 , we found that inhibition of α-Klotho protein significantly activated PI3K/Akt signaling in human primary chondrocytes in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 24 preclinical studies listed in Table 1, 20 were performed in animal models that required surgical destabilization of the joint. While these models are likely to be relevant to posttraumatic OA, their relevance to idiopathic OA, the majority manifestation, is unclear [21]. Likewise, two of the listed studies used MIA, an inhibitor of glycolysis, to induce OA.…”
Section: Preclinical Evaluation In Animal Models Of Osteoarthritismentioning
confidence: 99%
“…( 10 ) Although KOA is twice as likely to present in post-menopausal women than in men ( 11, 12 ), a recent systematic review showed that approximately 75% of murine studies of KOA only included males. ( 13 ) Of the few studies that did include females and menopause to study KOA, the predominant menopause model used was ovariectomy (OVX). ( 7, 14 ) However, the fidelity with which OVX recapitulates natural menopause is questionable.…”
Section: Introductionmentioning
confidence: 99%